Dream characters and the dream ego: an exploratory online study in lucid dreams - Schmidt, Steffen; Stumbrys, Tadas; Erlacher, Daniel (Dreaming, 2014)
Two exploratory online experiments were carried out to investigate the interaction between dream characters and the dream ego in lucid dreams. Lucid dreamers were recruited via an Internet page (http://klartraum.de). In Experiment 1, 15 participants (26.5 ± 10.2 years; 4 female, 11 male) provided 27 dream reports in which they asked dream characters 38 times to guess a number of fingers they show with their hands behind their back and then name another number of fingers that was visible to the dream characters. In Experiment 2, 7 lucid dreamers (24.3 ± 10.5 years; 2 female, 5 male) guessed 17 different numbers written down by 12 different dream characters. In Experiment 1, the hidden-type question was answered correctly by 19 out of 29 dream characters (66%). In Experiment 2, the correct number was successfully guessed in 10 out of 14 cases (71.4%). The results indicate that there is some form of connection between the dream ego and dream characters. Although the underlying mechanisms are not clear, the findings of this pilot study show that lucid dream studies are an efficient tool to provide knowledge about the characteristics of dream characters. (PsycINFO Database Record (c) 2014 APA, all rights reserved)
Gesehen am 14.08.2020